Students’ Perceptions of the Adoption and Use of Social Media in Academic Libraries: A UTAUT Study - Williams, Marion Lucille (Communicatio, Unisa Press, 2021)
This article reports on a study for which the Unified Theory of Acceptance and Use of Technology (UTAUT) served as a theoretical framework. The purpose of the qualitative exploration was to gain an understanding of students’ perceptions of the adoption of social media, namely Facebook and Twitter, in an academic library setting. The study applied the constructs as described by the UTAUT, namely, performance expectancy, effort expectancy, social influence and facilitating conditions, to explore students’ perceived behavioural intentions to use social media. A sample of 30 students were selected from two universities, one in Belgium (University of Antwerp) and one in South Africa (University of Limpopo), to gain better insight of the students’ perceptions regarding the adoption and use of social media, in particular Facebook and Twitter, by the academic libraries at these two universities. The study showed that the adoption of social media is positively influenced by effort expectancy, performance expectancy and social influence. A major challenge reported by most respondents at the University of Limpopo was poor internet access and the non-adoption of Facebook and Twitter, whilst respondents at the University of Antwerp had mixed feelings about the adoption of Facebook and Twitter for scholarly communication.
Article published in the Communicatio, © Unisa Press 2021, www.tandfonline.com/rcsa20
Keywords: Unified Theory of Acceptance and Use of Technology; academic libraries; Facebook; Twitter; Social media; Perception (Psychological); Online social networks; Students; Academic libraries-Effect of technological innovations of